Outcome of Teenage Pregnancy in the Niger Delta of Nigeria - Ayuba, Ibrahim Isa (Research and Publications Office of Jimma University, 2012)
BACKGROUND: Young maternal age at delivery has been proposed as risk factor for adverse pregnancy outcome, it occurs in all races, faiths, socioeconomic statuses, and regions. Teenage pregnancy can have serious physical consequences and teenage mothers are likely to be unmarried, poor and remain uneducated. The objective of the study was to evaluate risk factors associated with teenage pregnancy and compare the obstetric and fetal outcome to older parturient. METHODS: This is a retrospective study performed over a period of 4 Years (January 1, 2007 to December 31, 2010) in Niger Delta University Teaching Hospital Bayelsa State, Nigeria where data was retrieved from the hospital records. All teenage mothers (aged 13–19) who had delivery within the period were compared with 180 randomly selected deliveries in the older age group (20–32 years) over the same period. Variables of interest were the demographic characteristics of the women, their obstetric complications and the outcome. RESULTS: There were a total of 1341 deliveries during the study period, out which 83(6.2%) were teenagers. Teenage mothers were significantly more likely to be unbooked, (p = 0.000) Unmarried, (χ=26.2; p = 0.000) had significantly more preterm labor, (P=0.000) and Caesarean sections (P= 0.014). However, there was no difference in both the perinatal and maternal mortality rates between the two groups. CONCLUSION: Teenage pregnancy in the Niger Delta is concentrated among women with less formal education, who are unemployed, unmarried and with inadequate antenatal care and obstetric risks for poor pregnancy outcome. The provision an appropriate contraceptive method and to look with priority after any pregnancy occurring among this age group cannot be overemphasized.